Investigation of Natural Resistance to Fostemsavir and Lenacapavir in Naïve Primary Infections by Ultra-Deep Sequencing of near Full-Length HIV-1 Genomes - Elisabetta Lazzari; Gabriella Rozera; Roberta Gagliardini; Valentina Mazzotta; Lavinia Fabeni; Federica Forbici; Giulia Berno; Cristian Cosentino; Enrico Girardi; Andrea Antinori; Fabrizio Maggi; Isabella Abbate (Viruses)
Next-generation sequencing (NGS) of near full-length HIV genomes was performed to investigate natural resistance to Fostemsavir (FTR) and Lenacapavir (LEN) at the quasispecies level in nine naïve primary HIV infections harboring different HIV subtypes and recombinant forms. Reconstructed genomes provided a median (IQR) coverage for gag and env of 1710 (750–6063) and 1768 (871–5270), respectively. In the gp120 encoding region, the M426R variant was found with a frequency of 100% in two HIV subtypes B: one of these also showed the A204T variant at 100%. In the more conserved capsid coding region no mutations possibly related to LEN natural resistance were observed.